The Role of Technology-Enhanced Social Media in EFL Learning Among Secondary School Students (Comprehensive Journal of Science, 2025)
This exploratory study intended to explore the third year secondary schoolstudents’ perceptions about the role of technology-enhanced social media in developing Englishlanguage learning. It adopted an adapted questionnaire to collect data from students in order tosee how social media can affect various aspects of language skills, such as, students' languageskill improvement, motivation, confidence, and their learning attitudes. The participants included 55students from two secondary schools in Tripoli. The findings of the study showed that secondaryschool students generally viewed social media platforms as an important learning resource forlanguage learning which improved their vocabulary, communication, pronunciation, and listeningskills. The findings of the study also indicated that the role of these social media platformsincreased students' motivation and reduced their anxiety level when using social media forlearning. However, students perceived the role of social media in improving their grammar anderror correction as limited and weak. Furthermore, although many students preferred learningtrough social media over traditional learning methods, enjoyment levels varied considerably,indicating various learners' preferences. The study concluded that social media can serve as anadditional learning tool that supports independent learning but should be incorporated within formal
Keywords: Media, language, learning, perceptions, motivation, anxiety, autonomy